Using Office 365 : mastering Word, Excel, Outlook, Access, PowerPoint, Publisher and OneNote - Balter, Alison; Safari eBooks ([Place of publication not identified] : Que, 2016)
"Using Office 365: Mastering Word, Excel, Outlook, Access, PowerPoint, Publisher, and OneNote is an easy-to-understand, but comprehensive, 8+ hour video course that introduces viewers to the suite of apps that make up Office 365 and then explains exactly how to use these apps, including all the new features added as part of Office 2016."--Resource description page.
Presenter, Alison Balter.
Title and publication information from resource description page (Safari, viewed April 4, 2016).
Keywords: Microsoft Office; Business -- Computer programs; Electronic books